Informing public attitudes to non-potable water reuse – The impact of message framing. (15th November 2018) - Goodwin, D.; Raffin, M.; Jeffrey, P.; Smith, H.M.
Abstract: Water reuse is of increasing relevance for water-stressed regions but is often considered a contentious option. Research has shown that providing the public with information about reuse options can impact positively on its acceptability, although such impacts can be confined to specific groups. In this context, there is growing interest in understanding the impact of different forms and mechanisms of communication with the public around reuse. This contribution has investigated the use of video animations to communicate the safety of non-potable recycled water schemes. The aim of this study was to evaluate how different ways of framing messages about the safety of recycled water might impact on public attitudes. Participants were recruited in London (n = 689), UK, and randomly allocated to test and control groups, with the former being exposed to one of four video animations that used different frames to convey messages about recycled water safety. Surveys collected pre- and post-video message responses for dependent variables including the general acceptance of diverse non-potable recycled water uses, risk perceptions and trust. The findings complement existing knowledge on the impacts of different types of messaging on public attitudes to reuse schemes with important evidence for the positive impact of water safety communications framed in terms of compliance with water quality requirements. Contrarily, a positive attitudinal impact was not evident for safety message framed in terms of the selection of water treatment technology to remove contaminants nor in terms of non-potable water risks relative to other every-day risks. The results are of value to water resource planners looking to develop communication resources, as part of more comprehensive public engagement strategies, for improving perceptions of water reuse. Importantly, the findings help isolate the effects of specific message frames, and inform the debate on whether an increased understanding of risk positively or negatively influences willingness to support water reuse schemes. Graphical abstract: Image 1 Highlights: Study evaluated changes in attitudes to non-potable recycled water over time. Animated videos communicated water safety using different message frames. Evidence of frames impacting positively and negative on participants' views. A message framing typology is proposed to support future communication efforts.